An Effective Cable Sizing Procedure Model for Industries and Commerial Buildings - M. Pratap Nair; K. Nithiyananthan (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This paper mainly focuses on the cable sizing methods and calculation of electrical cables according to the various international standards. For instance, International Electrotechnical Commission (IEC), National Electrical Code (NEC), British Standard (BS) and Institute of Electrical and Electronics Engineers (IEEE). The basic philosophy underlying any cable sizing calculations are the same. The main objective of this research work is to develop effective cable sizing model for building services.